OPTIMALISASI PEMBERDAYAAN POTENSI SUMBER DAYA NASIONAL DI KALIMANTAN TIMUR GUNA MENGHADAPI ANCAMAN MILITER DI ALKI II - Slamet Hayat Riptanto; Syaiful Hasan (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2023)
In era of the industrial revolution 4.0 which is marked by a world that is increasingly borderless and full of uncertainty, these challenges are becoming increasingly complex. potential threats in the Indonesian Archipelagic Sea Lanes (ALKI II), particularly in the East Kalimantan region. Developments in the global, regional and national strategic environment have had a significant impact on the conditions and situation at ALKI II. One of the national strategic developments is the establishment of East Kalimantan as the new National Capital (IKN), which makes ALKI II an area vulnerable to military threats. Optimizing the empowerment of the potential of national resources in this region is very important in maintaining stability, sovereignty and state security in the maritime area, especially in ALKI II. To achieve this, steps are needed to be implemented by the central and regional governments to deal with maritime challenges more effectively and ensure the integrity and security of the maritime area. Changes in Indonesia's Center of Gravity (CoG), which was previously based in Jakarta, moved to the East Kalimantan region. In addition, the IKN location is at the ALKI II crossing which is an international waterway passed by military and civilian ships, and is close to the Flight Information Region (FIR) of a neighboring country and within the cruising radius of a neighboring country. Intercontinental Ballistic Missile (ICBM) from China on the northern side of Indonesia. Therefore, it is necessary to implement a solid defense architecture in the East Kalimantan IKN and optimize the empowerment of the potential of National Resources in order to deal with military threats and support national defense at sea.